Theory of Planned Behavior: Implikasi Teori Dalam Menjelaskan Minat Belajar Mahasiswa Pada Mata Kuliah Akuntansi Keuangan - Kharisma Nugraha Putra; Hidayati, Hidayati; Merisa Oktaria (Edunomics Journal, 2024)
The purpose of this research is to explain the implications of the Theory of Planned Behavior in elucidating students' interest in learning financial accounting courses by adopting the framework of the Theory of Planned Behavior, which includes attitude toward behavior, subjective norms, perceived behavioral control, and learning interest. The sample in this study consists of undergraduate students in the economic education program at the University of Palangka Raya who are actively enrolled in the even semester of the 2023/2024 academic year. The data collection method is a survey using a questionnaire as the research instrument. The total sample size is 69. Data is analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS) with the WarpPLS 8.0 program. The results of the study indicate that the Theory of Planned Behavior is a relevant theory in explaining students' learning interest. The findings show that attitude toward behavior and subjective norms positively influence students' interest in learning financial accounting courses, while perceived behavioral control does not affect students' interest in learning financial accounting courses